A Comparative Study on Adsorbing Gaseous Formaldehyde with Novel Biomass Activated Carbons from Agriculture Wastes at Ambient Temperature. Issue 1 (November 2020) - Gao, Lei; Li, Xian; Liu, Yingyun; Xie, Jinke; Li, Caiting
Abstract: To remove gaseous formaldehyde (HCHO) and rationally utilize agriculture wastes, chemical activation method using ZnCl2 as activating agent was employed to develop high-class biomass activated carbons (BACs) derived from agricultural straws for HCHO removal at ambient temperature. Proximate analysis and ultimate analysis testified that these agricultural straws were appropriate BACs precursors. BACs' physicochemical properties were characterized by BET, SEM, FTIR and TGA, which demonstrated BACs with large specific surface area had the potential as ideal adsorbents. Systemic tests investigated the effects of activating agent (ZnCl2 ) and the concentrations of O2 and HCHO on adsorption performances of BACs, and compared them with two commercial activated carbons (CACs). Results showed ZnCl2 brought enormously positive effects but O2 had a prohibitive effect on the adsorption performance. BACs exhibited better performance than CACs, and BACM (BAC derived from maize straw) could obtain more than 80% removal efficiency under 1ppm HCHO after 40h. Desorption and regeneration tests were conducted to evaluate the security of the adsorbent and recycle regenerated adsorbent. The desorption temperature all above 50°C could ensure use security indoors. Saturated BACM through 1 or 2 run regeneration still exhibited better adsorption performance compared with virgin CAC from coal, indicating that the regeneration was significantly meaningful in practical application.